Síntese e caracterização de ligas nanocristalinas à base de cobre e zircônio com elevada capacidade de formação de estado vítreo - Castilho, Amanda Ventura (2017)
In this work, copper – zirconium rich compositions with high glass forming ability were selected according to literature review and computational thermodynamics simulations. Arc melting and suction casting (solidification out of equilibrium) processes were performed in order to produce nanocrystalline materials. X-ray and scanning electron microscopy results showed that samples produced with arc melting followed by suction casting processes leads to visualization of nanometric phase and have more refined microstructures if compared with samples produced by arc melting merely. Differential scanning calorimetry data are consistent with the crystallization of present amorphous phase, in samples produced by solidification out of equilibrium. The relation between microstructure refinement and investigated properties (nanohardness, corrosion resistance and hydrogen interaction) were performed through nanoindentation, potentiodynamic polarization and hydrogenation followed by thermal dessorption spectrometry experiments. Nanoindentation results did not show appreciable difference between samples produced conventionally and with suction casting. Potentiodynamic polarization curves suggest less dissolution of the material in acid after microstructure refinement. Thermal dessorption spectrometry revealed that suction casting enhances the bonding energy of hydrogen in ZrH2 phases.